The Existance of a Mandatory Will for Adopted Children in Fiqh and Islamic Compilation Law - Irfan Abdul Hamid; M. Adli; Ilyas Yunus (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
This research was conducted to observe the Islamic scholars’ perception on last wills and die. Then for the group of Islamic scholars, who disagree giving legacy to adopted children, stated that the last will and testament in Islamic testaments for adopted children by using normative and empirical juridical methods. The results showed that the ‘ulama’ (islamic scholars) who stated the giving mandatory will to the adopted children do not contradict Islamic Law. This is justified in order to save them from unattended lives if the heir or parents jurisprudence is not solely for adopted children. In fact, wills and testament in Islamic Law distribute other than inheritance. The providing legacy to an adopted child is carried out because it relies on the principle of ‘mashlahah mursalah’ (something benefits other) which is to anticipate the ignorance to adopted child after his adoptive parent dies